Juan de Torquemada, exponent of infallibility in the fifteenth century: A study of conciliar speeches leading to eventual synthesis of doctrine - Mary Edith, Sister (University of Ottawa (Canada), 1950)
Abstract not available.
Keywords: Religion, History of.